Intussusception in Premature Baby: Unusual Cause of Bowel Obstruction and Perforation - Kanokkarn Tepmalai; Thanyaluk Naowapan; Jesda Singhavejsakul; Mongkol Laohapensang; Jiraporn Khorana (EL-Med-Pub, 2016)
Intussusception in a premature baby is a rare condition. We report a male preterm infant, who developed abdominal distension and abdominal wall erythema. He was operated with suspicion of NEC but an ileo-ileal intussusception and intestinal perforation were encountered at operation.